Geofluids as a possible unconventional tool for seismic hazard assessment - Martinelli, Giovanni; Pierotti, Lisa; Facca, Gianluca; Gherardi, Fabrizio (Frontiers in Earth Science, 2023)
In recent decades, phenomenological methods known as Recognition of Earthquake-Prone Areas (REPA) were set up for identifying potential sites of powerful earthquakes. The information on potential earthquake sources provided by the REPA method is an essential part of seismic hazard assessment methodology. For the first time, we have combined global-scale information on the geographic occurrence of geofluids with global-scale information on earthquake occurrence, heat flow distribution, and S-wave dispersion, to gain insights into the evolution of local stress-strain fields. We focused on areas characterized by the occurrence of thermal waters and/or by the release of deep-seated gases, as traced by the isotope composition of associated helium. We noticed that the geographic distribution of these geofluids could serve as an indirect indicator of crustal permeability anomalies generated by crustal deformation procedures. This study proposes adding geofluids to the list of fundamental geological parameters to be considered in hazard assessment research.